PERANAN BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA DALAM PENEMPATAN PEJABAT STRUKTURAL DI KABUPATEN ALOR PROVINSI NUSA TENGGARA TIMUR - Fatimah, Yeti (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2019)
Employee placement in Indonesia has not yet fully applied the principle of “The Right Man On The Right Place”. This causes the performance of government employees and organizations are not optimal. On this basis, the author wants to know the role of the Human Resources and Human Resources Development Agency in the placement of Structural Officials, the obstacles encountered and efforts to overcome these problems based on the Law of the Republic of Indonesia number 5 of 2014 and the opinion of Soekanto 2009 (212-213) relating to the role of the Personnel Agency and the Development of Apparatus Resources in the placement of structural officials. This research uses a qualitative method with an inductive approach. Data collection uses observation, interview and documentation techniques. While in analyzing data, the authors use data eduction techniques, data display and verification. Results of the Discussion, the Human Resources and Human Resources Development Agency of Alor Regency of NTT has performed its role well, namely to propose the placement of employees according to their competence and educational background. However, there are still obstacles faced by the intervention of the authority of the Regional Head in the placement of employees. The Human Resources and Human Resources Development Agency has made efforts to overcome these obstacles both formally and informally.